Actualización del manejo de metástasis encefálicas - Zomosa R., Gustavo; González J., Lucas; Miranda G., Gonzalo; Galleguillos E., María Fernanda; Arellano A., Anita (Revista Hospital Clínico Universidad de Chile, 2018)
rain metastases represent a critical stage of oncological disease and its frequency is increasing over the recent years. The treatment of brain metastases has moved from a conservative approach to an active management that should be individualized for each patient: in case of single brain metastasis, surgery or radiosurgery should be considered as first option of treatment; in case of multiple lesions, whole-brain radiotherapy is the standard of care. The aim of this review is to present general aspects including new approaches in management of patients with brain metastases.